Game Memoria sebagai Inovasi Digital Terapi Kognitif Pencegahan Demensia bagi Lansia: Studi Pengujian Prototipe Skala Industri - Khairunisa, Yuyun; Bayu Dwi Nurwicaksono; Deni Kuswoyo (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The purpose of this article is to describe the results of memory game testing as a digital innovation of cognitive therapy in preventing dementia for the elderly. Dementia is a degenerative disease that attacks cognitive function in the elderly. Until now, no cure for the disease has been found; however, the risk and symptoms can be reduced through various therapies that stimulate and improve cognitive function. Smart games can be an effective tool for helping elderly individuals engage in cognitive and physical exercise. Games can stimulate the brain to prevent and slow the progression of dementia. The method used is Community-Based Participatory Research (CBPR). The stages include the formation of partnerships, the implementation of collaborative and participatory research, and the dissemination of findings. The partnership was formed with the community of True Crossword Puzzle Lovers (Petition). The design of CBPR involved the elderly in Srengseng Sawah, the curator of TTS Kompas Book Publisher, game practitioners from PT Terminal Koding, and PT Karya Jasa Digital. In its implementation, the team identified elderly health problems, designed the TTS, sought expert validation for the TTS, developed the TTS in a digital game format, tested the feasibility of the games with industry practitioners, and disseminated the games to the public. The results of the usability test, based on ISO 9241-11, indicate a positive level, with usability criterion at 70%, application ease of use criterion at 76.8%, ease of learning the application at 78%, and user satisfaction at 80.4%. Testing was also conducted on the main users of the game, specifically older people and those over 50 years old. The results of this prototype test showed that 85% of older people reported being satisfied, with a 95% level of sensitivity to memory improvement. Thus, this Memoria game can be applied as an alternative medium for dementia prevention as well as a digital innovation for cognitive therapy.